Aggressive Communication Style as Predictor of Cyberbullying, Emotional Well-being, and Personal Moral Beliefs in Adolescence - Salgado Pereira, Nádia (2022)
Different forms of verbal aggression are often presented in cyberbullying and are used to harm others in online communication. This study proposed to understand the influence of an aggressive communication style on adolescents’ intentions to engage in cyberbullying, their emotional well-being, and personal moral beliefs. A convenience sample of 218 adolescents (Mage = 14.67, SD = 0.84, 53% girls) in Portugal responded to questionnaires. Structural equation modeling analyses were conducted to test mediating effects. An aggressive communication style may lead adolescents to perceive cyberbullying behavior as fair, and to decrease their emotional well-being. Moreover, this communication style may contribute to adolescents’ intentions to engage in cyberbullying, and whether they believe this type of behavior is fair or unfair may determine those intentions. These findings contribute to an understanding of determiners of cyberbullying and the provision of insights to develop school interventions in this field.